Flipped laboratory classes: Student performance and perceptions in undergraduate food science and technology. Issue 4 (23rd November 2021) - Mshayisa, Vusi Vincent; Basitere, Moses
Abstract: In STEM (science, technology, engineering, and mathematics) courses, undergraduate laboratory classes are vital for students to develop competencies such as critical observation, collaboration, critical thinking, technical, and problem‐solving skills. Thus, for students to successfully acquire these competencies, preparation for laboratory classes is essential. This study aimed to explore the students' performance and perceptions of online pre‐laboratory videos and quizzes in undergraduate food science and technology. Quantitative data on student usage statistics of the videos, student performance in online quizzes and practical reports scores and student perceptions were analysed to provide a detailed perspective of the course. The students' performance was above 60% in all pre‐lab quizzes for both the 2018 and 2019 cohorts. The average pre‐lab video views were higher in the 2019 cohorts compared to the 2018 cohort. The majority of the students felt that the topics were well explained in the videos (M = 4.25 ± 0.84) and it was easy to learn from the videos (M = 4.31 ± 0.76). In terms of students perceptions, a strong positive correlations were found between course organisation and motivation and self‐efficacy (r = 0.86, p  < 0.05); course engagement and motivation and self‐efficacy (r = 0.82, p  < 0.05). The strongest positive correlation was between course organisation and online engagement (r = 0.95, p  < 0.05). The results of this study suggest that the introduction of multimodal/digital preparation resources (pre‐lab videos and online quizzes) was positively received and benefited the students. Students have engaged enthusiastically with these resources and completed the majority of the tasks set. These findings will further expand research directed towards student perception of the lab experience and aid in the adaptation of food science and technology curriculums to accommodate both student and university needs.